2019
DOI: 10.7554/elife.44830
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal integration in the adult mouse olfactory bulb is a non-selective addition process

Abstract: Adult neurogenesis in the olfactory bulb (OB) is considered as a competition in which neurons scramble during a critical selection period for integration and survival. Moreover, newborn neurons are thought to replace pre-existing ones that die. Despite indirect evidence supporting this model, systematic in vivo observations are still scarce. We used two-photon in vivo imaging to study neuronal integration and survival. We show that loss of new neurons in the OB after arrival at terminal positions occurs only a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 56 publications
(123 reference statements)
9
71
1
Order By: Relevance
“…It was shown in the OB that olfactory training (Mouret et al, 2008) or overexpression of NaChBac (Lin et al, 2010) could increase recruitment during synaptic integration. In sharp contrast, it was recently demonstrated that in physiological condition selection during synaptic integration is nearly absent (Platel et al, 2019) pointing to a first selection step occuring before integration (Biebl et al, 2000;Platel et al, 2010). In agreement with these latter studies, our results suggest that survival of neuroblasts during radial migration is dependent on neuronal activity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It was shown in the OB that olfactory training (Mouret et al, 2008) or overexpression of NaChBac (Lin et al, 2010) could increase recruitment during synaptic integration. In sharp contrast, it was recently demonstrated that in physiological condition selection during synaptic integration is nearly absent (Platel et al, 2019) pointing to a first selection step occuring before integration (Biebl et al, 2000;Platel et al, 2010). In agreement with these latter studies, our results suggest that survival of neuroblasts during radial migration is dependent on neuronal activity.…”
Section: Discussionsupporting
confidence: 92%
“…For example, increasing neuronal activity via olfactory training (Mouret et al, 2008) or by over-expression of the bacterial sodium channel NaChBac expression (Lin et al, 2010) enhance the number of newborn neurons integrated. By contrast, sensory deprivation via naris occlusion decreased the survival of newborn neurons in the OB (Saghatelyan et al, 2005;Yamaguchi and Mori, 2005;Platel et al, 2019).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Thousands of ABCs migrate into the OB every day but many of them are thought to be eliminated by programmed cell death [17][18][19][20][21][22] (but see ref. 23). According to data obtained in bromodeoxyuridine (BrdU) incorporation experiments, elimination of ABCs mainly happens between 15 and 45 days after birth [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…In the postnatal and adult rodent forebrain, new interneuron precursors are continuously generated by neural stem cell populations along the walls of the lateral ventricles. After their amplification in the subventricular zone (SVZ) and long-distance migration via the rostral migratory stream (RMS), they are added to the preexisting circuitry of the olfactory bulb (OB) Whitman and Greer, 2009;Platel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%